Evaluación de sensibilidad antibiótica de uropatógenos de pacientes que acudieron al laboratorio Quintanilla de Trujillo, febrero 2017- febrero 2018 - Capuñay Reyes, Patricia Pamela (2019)
The objective of this report was to evaluate the antibiotic sensitivity of uropathogens of patients who attended the Quintanilla de Trujillo laboratory, February 2017-February 2018. There were 1036 patients with positive urine culture tests, using the disc agar dissemination method, considering: age group, gender, most frequent germ, sensitivity patterns and resistance patterns; the method was descriptive and cross-sectional. The frequency of UTI according to gender was higher in women than in men; age group, older than 21-30 years, with the germ Escherichia coli 23%; Klebsiella sp 3%; Proteus sp 32%; Staphylococcus saprophyticus 27%; Streptococcus sp 50%; respectively. According to most frequent germs, the highest incidence was with E. coli, followed by Proteus sp. of the total of the 5 germs. According to sensitivity patterns, the drugs most sensitive to these germs were: Amoxicilina + Ac. clavulanic, Meropenem, Imipinem, Ciprofloxacin, Gentamicin, Amikacin, Ceftazidime, Cefuroxime. According to resistance patterns, the drugs most resistant to these germs were: Nalidixic acid, Levofloxacin, Penicillin, Erythromycin, Ampicillin. It is concluded that during the study period a higher frequency of UTI was observed in women, aged between 21-30 years, and nowadays with medicines for the treatment of UTI within reach of the entire population